Long-term indwelling double-J stents: Bulky kidney and urinary bladder calculosis, spontaneous intraperitoneal perforation of the kidney and peritonitis as a result of 'forgotten' double-J stent - Stojković Ivica; Stevanović Dragan (Vojnosanitetski Pregled)
Background. The first double-J (DJ) stents were manufactured in 1978. Their J-shaped tips efficiently prevent their migration from kidneys and from the urinary bladder. Nowadays, DJ stents are in common use because they provide efficient and relatively safe urinary derivation between the kidney and the urinary bladder. We report this case with the aim to point out possible serious complications with long-term indwelling stents. Case report. The patient was admitted to hospital five years after the placement of DJ in a bad general condition, with symptoms of peritonitis. Radiological examination (plain abdominal film, computerized tomography, excretory urogram and cystography) showed bulky calculosis at each tip of the stent, affunctional right kidney, vesicoureteral reflux through the DJ stent and ureter all the way to the right kidney, as well as a large amount of turbid liquid in the abdomen. In the course of the operation, the bulky stone with the DJ stent was removed form the urinary bladder, followed by a large amount of turbid liquid extracted from the abdomen. During adhesiolysis, a small intraperitoneal perforation through which a tip of the stent prolapsed, was found on the upper pole of the kidney. After that, nefrectomy was performed. The patient was discharged 18 days after the surgery. Conclusion. There are usually no complications with shortterm DJ stent urinary drainage. However, indwelling DJ stents can cause serious complications, such as migration, incrustration and fragmentation. DJ indwelling should be as short as possible. If indwelling stenting is necessary, the DJ stent should be replaced with a new one in due time, or another kind of derivation should be performed. Careful monitoring of patients could exclude any possibility of a stent being forgotten at all.